Re-ranking for web image search - Ngoh, Him Lim. (2012)
The utilization of Internet as a tool for social interaction has been the latest trend in the recent years. Social networking websites have created a new way to interact and stay in contact with people. Users can now easily share information online by adding texts or uploading pictures to these sites. The ease in sharing has led to the increase of images on the Internet. As such, the retrieval of relevant images from a large collection is now an important topic. One of such retrieval systems is the well-known Text-Based Image Retrieval. Its retrieval performance is however dependent on the textual features provided which gives poor performance when the textual features of the images are sparse and noisy.